FV9. Nerve ultrasound parameters as biomarkers in CIDP – A prospective 12 months follow-up study. Issue 8 (August 2018) - Grimm, A.; Härtig, F.; Winter, N.; Lerche, H.; Axer, H.; Décard, B.
Abstract : Importance: Maintenance or cessation of therapy is an essential question in immune-mediated neuropathies. However, therapeutic biomarkers are of restricted validity, as for example nerve conduction studies (NCS). Ultrasound of the nerves has proven its potential role in the diagnoses of neuropathies; however, its usefulness as a prognostic biomarker is still unclear. Objective: To determine whether ultrasound scores and ultrasound morphology are suitable biomarkers for therapeutic response and clinical development. Design: Twelve months follow-up observational study. Setting: University Hospital Tübingen, Basel and Jena. Participants: 79 (including 34 therapy-naïve) patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) fulfilling EFNS/PNS-guidelines. Exposures: Ultrasound, NCS parameters, and clinical scores (medical research council sum score, MRCSS, and inflammatory neuropathy cause and treatment (INCAT) disability score) at screening visit and after 3, 6, and 12 months. Main outcome: Clinical, ultrasound and NCS change over 12 months and its correlation. Results: 90% CIDP patients revealed multifocal nerve enlargement as evaluated by the ultrasound pattern sum score (UPSS). The UPSS at baseline did only partially correlate with clinical scores (MRCSS: r 2  = 0.013, p  = 0.332; INCAT: r 2  = 0.053, p  = 0.048), whereas the NCS data correlated significantly with both ( r 2  = 0.410, and r 2  = 0.443, p  < 0.001). In contrast, clinical development correlated significantly with changes in ultrasound parameters (correlation of UPSS with MRCSS and INCAT changes: r 2  = 0.272 and r 2  = 0.343, p  < 0.0001), whereas NCS changes did not ( r 2  = 0.054 and r 2  = 0.042, p  > 0.25). Furthermore, classifying the ultrasound parameters of nerve, fascicle size and echointensity into three major subtypes, could be shown to be clinically useful biomarkers. Hypoechoic enlarged nerves (class 1), which are found in therapy-naïve and chronic CIDP variants (65.5:34.5%), predict the best therapeutic response as an improvement of clincal scores (predictive value up to 0.75). In contrast, enlarged nerves with hyperechoic fascicles or perifascicular tissue (class 2) and those with no or only slighly enlarged nerves (UPSS < 5 points, class 3), both showed a limited treatment response (predictive value up to 0.43) ( X 2 -test in favor of class 1: p  < 0.05). Conclusion and relevance: our results indicate that (i) the quantification of ultrasound signals by the UPSS is a suitable therapeutic biomarker over 12 months, and that (ii) ultrasound-guided nerve morphology may predict therapeutic response.